Etude phytochimique et l’activité antidiabétique de l’Atriplex halimus L chez les rats wistar - BELABACI, Fatima; Zohra BELABACI, Senia (My University, 2019)
Diabetes mellitus is a very common disease in the world. It is treated by insulin and oral antidiabetic agents that can cause serious side effects. For this reason and because of their unavailability in some cases, diabetes is cured by herbs. This work aims to evaluate the antidiabetic activity of Atriplex halimus .L, an plant widely used against diabetes mellitus. We studied the aerial part that was used to prepare a crude aqueous extract (CAE). . CAE there from, subject to the phytohemical study were tested for their antidiabetic activity in 80mg/kg streptozotocin induced-diabetic Wistar rats. The results show the presence of several chemical compounds in CAE, mucilages, tanins, saponins, amino acids, flavonoids, cardiac glycosides and alkaloids. CAE at 100mg/kg significantly reduces fasting hyperglycemia and improves oral glucose tolerance in rats. The effects of the seven fractions of CAE at 200 mg/kg .At the tested doses, three fractions showed a positive effect on fasting hyperglycemia and the oral glucose tolerance, two act only on fasting hyperglycemia, while the remaining have no effects on diabetes. It is obviously clear that Atriplex halimus.L precisely CAE regulates certain disturbances of diabetes. This property is maintained in the prepared fractions. It is, therefore, crucial to choose the most active fraction for further chemical fractionation and evaluation of the antidiabetic activity.
Keywords: aqueous extract; streptozotocin; hyperglycemia; rat wist; Atriplex halimus .L